Joint universality of the Riemann zeta-function and Lerch zeta-functions - Laurinčikas, Antanas; Macaitienė˙, Renata (Nonlinear Analysis: Modelling and Control, 2013)
In the paper, we prove a joint universality theorem for the Riemann zeta-function and a collection of Lerch zeta-functions with parameters algebraically independent over the field of rational numbers.
Keywords: Lerch zeta-function; Riemann zeta-function; limit theorem; universality